2005
DOI: 10.2337/diacare.28.7.1574
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Low-Literacy Diabetes Education Computer Multimedia Application

Abstract: OBJECTIVE -To evaluate a clinic-based multimedia intervention for diabetes education targeting individuals with low health literacy levels in a diverse population.RESEARCH DESIGN AND METHODS -Five public clinics in Chicago, Illinois, participated in the study with computer kiosks installed in waiting room areas. Two hundred forty-four subjects with diabetes were randomized to receive either supplemental computer multimedia use (intervention) or standard of care only (control). The intervention includes audio/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
262
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(283 citation statements)
references
References 31 publications
10
262
0
2
Order By: Relevance
“…Early studies therefore responded by re-writing health materials at a simpler level or following other design principles to enhance reading comprehension; an approach found to have limited success. 7,8 Still lacking a deeper understanding of the problem, recent investigations have tested comprehensive strategies with more promising results. [9][10][11] However, as these were multi-faceted interventions targeting system complexity, it is difficult to isolate the true reason for improvement.…”
Section: Objectivementioning
confidence: 99%
“…Early studies therefore responded by re-writing health materials at a simpler level or following other design principles to enhance reading comprehension; an approach found to have limited success. 7,8 Still lacking a deeper understanding of the problem, recent investigations have tested comprehensive strategies with more promising results. [9][10][11] However, as these were multi-faceted interventions targeting system complexity, it is difficult to isolate the true reason for improvement.…”
Section: Objectivementioning
confidence: 99%
“…To do this will be particularly challenging, as many tools that have already been developed specifically for lower literate audiences have not been entirely successful. Gerber et al demonstrated a lack of significant knowledge gains for educating patients on diabetes self-care concepts using state-of-the-art multimedia (Gerber, 2005), and early efforts by Davis and colleagues found plain language print health information to produce only minimal improvement compared to existing brochures for polio vaccination (Davis, 1998). While guidance is available throughout various sources as to how best to create and field test plain language health information materials for diverse patient groups, there remains a need to consolidate recommendations, systematically assess the efficacy of newly available materials, and offer streamlined means to disseminate them at low or no cost to health care providers and systems.…”
Section: Improve Patient Educationmentioning
confidence: 99%
“…Medical researchers have also developed several health education kiosks for placement in public spaces or clinic waiting rooms. One example is a waiting room touch screen kiosk for diabetes education, designed to accommodate patients with inadequate health literacy [12]. The system featured simplified navigation buttons and multimedia educational content and testimonials tailored to users' prior computer experience, learning styles and ethnicity.…”
Section: Introductionmentioning
confidence: 99%